The Effects of Reward Systems on Employee Performance Case of MTN Uganda Ntinda Branch. - Patrick Odida (Uganda Christian University, 2023)
The purpose of this study was to establish the effects of reward systems on employee performance at MTN Uganda Ntinda branch. The study was guided by three objectives which are to assess the effects of fringe benefits on performance of employees at MTN Uganda, to find out effects of work life balance on employee performance, to assess the effects of skills development on performance of employees at MTN Uganda. A correlation design was employed and a sample of 58 respondents participated in answering questionnaires and the findings were computed to a significant figure of 0.491 and this showed that relationship between the independent variables fringe benefits, work life balance and skills development with the dependent variables productivity rates , time management and workload coverage was moderate positive relationship which can be interpreted as an increase in the independent variable leads to an increase in the dependent variable but the relationship is not strong enough to make prediction about one variable based on another .The researcher also concluded that are very essential in human resource management as they act as motivators and performance enhancers and the company should fully endorse them ,the researcher therefore recommended that the company gives rewards right from top management down to the sim selling agents as they deal directly with the core product which is sim cards ,the researcher also recommended that the company puts into consideration Maslow’s theory of needs when rewarding its employees because different employees require different needs to meet their satisfaction levels and lastly the researcher recommends that the company executives work hand in hand with different levels of management that is top, middle and line managers when planning to issue out rewards as these know the needs of their subordinates
This is a dissertation.